Whole transcriptome analysis of trophoblasts under hypoxia. (January 2022) - Sun, Jintang; Song, Bingfeng; Ban, Yanli; Ma, Chao; Sun, Jia; Ai, Dan; Nan, Zhaodi; Wang, Lijie; Qu, Xun
Abstract: Introduction: A physiological hypoxia environment exists at maternal-fetal interface during early pregnancy. In addition, there is a pathological hypoxic microenvironment in patients with preeclampsia. Therefore, investigating the hypoxic adaptation and the effects of hypoxia on trophoblasts transcriptome is helpful to better understand the function and regulatory mechanism of trophoblasts at the maternal-fetal interface. Methods: Trophoblast cell line HTR-8/SVneo was cultured under normoxia and hypoxia for 24 h, the full transcriptome was analyzed via RNA-Seq. GO and KEGG enrichment were performed on differentially expressed mRNA, adjacent genes of differentially expressed lncRNA, host genes of differentially expressed circRNA and target genes of differential expressed miRNA. Results: The results showed that hypoxia differentially regulated 373 mRNAs, 334 lncRNAs, 71 circRNAs and 33 miRNAs. GO and KEGG enrichment showed that hypoxia negatively regulated TLR3 and PI3K-Akt signaling pathways. Consistently, we found hypoxia significantly inhibited TLR3 agonist-induced cytokines expression and the phosphorylation of Akt and mTOR. Discussion: Our study obtained the full transcriptome data and potential regulatory network of trophoblasts under hypoxia, providing supportive data for revealing the function of trophoblasts. Highlights: Analyze the whole transcriptome of HTR-8/SVneo under hypoxia for the first time. Hypoxia negatively regulated TLR3 signal pathways of HTR-8/SVneo. Hypoxia inhibited PI3K-Akt and mTOR pathway of HTR-8/SVneo.